Common factors among a group of filipino male overachievers - Hechanova, Jesse, FSC (Animo Repository, 1974)
This study attempts to find out the common factors among a group of overachievers, through the academic, social, psychological and teacher's description approach. It also aims to shed more knowledge on the possible contributive factors to overachievement behavior, especially on the Philippine setting. This knowledge could hopefully help educators develop and encourage the potential of their students, to prevent or diminish underachievement behavior and also to help the school in their admission programs. The subjects of this study were 44 male first year high school students whose grade point average in their first semester was more than one standard error of estimate above their predicted grade point average using their score on a standardized test of academic ability as predictor. The subjects were given a series of tests, questionnaires and were interviewed to provide knowledge on the factors being studied. Responses to these tests, and questionnaires were checked and recorded accordingly so as to answer the questions and hypotheses presented on the first part of this paper. With the use of an appropriate statistical test of significance of difference (chi-square) the common factors among the group were known. The result showed that the following are the common factors among this group of overachievers : positive self image, good study habits, good sense of personal worth, sense of belonging, desirable social standards, good family, school and community relations, clear sense of direction or goals, definite motivations, pleasant and secure childhood, belonging to smaller families, having parents who are well educated, having strict discipline, residing in the city proper or near the school, and belonging to the same class groupings as the other overachievers.